Negative Emotion Does Not Modulate Rapid Feature Integration Effects - Truebutschek, Darinka; Egner, Tobias (Frontiers in Psychology, 2012)
Emotional arousal at encoding is known to facilitate later memory recall. In the present study, we asked whether this emotion-modulation of episodic memory is also evident at very short time scales, as measured by “feature integration effects,” the moment-by-moment binding of relevant stimulus and response features in episodic memory. This question was motivated by recent findings that negative emotion appears to potentiate first-order trial sequence effects in classic conflict tasks, which has been attributed to emotion-modulation of conflict-driven cognitive control processes. However, these effects could equally well have been carried by emotion-modulation of mnemonic feature binding processes, which were perfectly confounded with putative control processes in these studies. In the present experiments, we tried to shed light on this question by testing explicitly whether feature integration processes, assessed in isolation of conflict–control, are in fact susceptible to negative emotion-modulation. For this purpose, we adopted a standard protocol for assessing the rapid binding of stimulus and response features in episodic memory (Experiment 1) and paired it with the presentation of either neutral or fearful background face stimuli, shown either at encoding only (Experiment 2), or at both encoding and retrieval (Experiment 3). Whereas reliable feature integration effects were observed in all three experiments, no evidence for emotion-modulation of these effects was detected, in spite of significant effects of emotion on response times. These findings suggest that rapid feature integration of foreground stimulus and response features is not subject to modulation by negative emotional background stimuli and further suggest that previous reports of emotion-modulated trial–transition effects are likely attributable to the effects of emotion on cognitive control processes.